The derivatives instruments and bank stability in Malaysia: evidence from recent financial crisis / Juhariah Saad - Saad, Juhariah (2016)
Bankruptcy that affects the failure operation of the bank institution has been an important topic between the bankers and economist. The derivatives instruments are the yardstick to measure the performance of bank stability. This study attempts to explore the derivatives instruments and bank stability in Malaysia evidence from recent financial crisis. Eight commercial banks has been the subject for this study ranging from 2006 until 2014. The local commercial bank geographically in Malaysia selected for this study. The bank's financial statement has been the main sources for the study and the panel data analysis has been carried out to obtain the results for this empirical study. This research use secondary data focused on the quantitative approach. The study conducted test namely pooled Ordinary Least Square (OLS) model to determine the result from the model to be used in this studies. The empirical analysis supported three independent variables used in this studies which are option, size and efficiency showed a positive siY1ificant relationship with the dependent variable. Meanwhile, tier-I and credit-risks indicates insignificant movement with the bank stability.